Compliance with Antibiotic Prophylaxis in Obstetric and Gynecological Surgeries in Two Peruvian Hospitals - Arteaga-Livias, Kovy (2023)
Introduction: Surgical site infections (SSI) can be as high in gynecology and obstetrics surgeries compared to other areas. Antimicrobial prophylaxis is an effective tool in the prevention of SSIs; however, it is often not adequately administered, so this study aimed to understand the compliance and factors associated with the use of the clinical practice guidelines for antibiotic prophylaxis in gynecological surgeries in two hospitals in the city of Huanuco, Peru. Methods: An analytical cross-sectional study of all gynecologic surgeries performed during 2019 was performed. Compliance was determined based on the antibiotic chosen, dose, administration time, redosing, and prophylaxis duration. Age, hospital of origin, presence of comorbidities, surgery performed, as well as its duration, types of surgery, and anesthesia were considered as related factors. Results: We collected 529 medical records of patients undergoing gynecological surgery with a median age of 33 years. The prophylactic antibiotic was correctly indicated in 55.5% of cases, and the dose was correct in 31.2%. Total compliance with the five variables evaluated was only 3.9%. Cefazolin was the most commonly used antibiotic. Conclusion: Low compliance with the institutional clinical practice guidelines for antibiotic prophylaxis was identified, showing that antimicrobial prophylaxis in the hospitals studied was inadequate.